2018
DOI: 10.1186/s12885-018-4706-x
|View full text |Cite
|
Sign up to set email alerts
|

TRH site-specific methylation in oral and oropharyngeal squamous cell carcinoma

Abstract: BackgroundThe incidence of oral squamous cell carcinoma (OSCC) continues to increase each year. Clinical examination and biopsy usually detect OSCC at an advanced stage that is difficult to treat, leading to poor prognosis. DNA methylation pattern is tissue specific and has emerged as a biomarker for the detection of cancers of tissue origin. Herein, we aimed to discover a novel site-specific methylation marker for OSCC.MethodsWe selected OSCC datasets analyzed using the IlluminaHumanMethylation27 BeadChip fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Oral squamous cell carcinoma (OSCC) is recognized as the most common phenotype of oral cancer, accounting for approximately 3% of the malignancies worldwide [1]. Annually, there are more than 300,000 patients diagnosed with OSCC worldwide, which is within the top 10 morbidity of all cancers and continues to increase [2][3][4]. Consumptions of tobacco and alcohol are responsible for almost 90% of the OSCC cases, while oral hygiene, human papillomavirus, and dental status are also considered as the risk factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is recognized as the most common phenotype of oral cancer, accounting for approximately 3% of the malignancies worldwide [1]. Annually, there are more than 300,000 patients diagnosed with OSCC worldwide, which is within the top 10 morbidity of all cancers and continues to increase [2][3][4]. Consumptions of tobacco and alcohol are responsible for almost 90% of the OSCC cases, while oral hygiene, human papillomavirus, and dental status are also considered as the risk factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the Alu and TRH site-specific methylations for OSCC detection. However, the cutoff values of both markers have to be evaluated for cancer [14,21]. In this study, the calculation of cg22881914 NID2 methylation clearly indicated totally zero value in the normal oral epithelium, and eventually, the samples were used up to a concentration of 10 ng/μl.…”
Section: Discussionmentioning
confidence: 84%
“…The bioinformatic approach was previously reported [14]. In brief, we collected the methylation microarray data of GPL8490 (Illumina® HumanMethylation27 Bead-Chip Kit, Illumina Inc., San Diego, CA, USA) related to the following keywords: head and neck cancer, head and neck squamous cell carcinoma (HNSCC), OSCC, and normal oral epithelial cell.…”
Section: Bioinformaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, early diagnosis is potentially achieved and consequently leads to a better prognosis. Different papers focused on promoter hypermethylation and show that specific genes of patients with head and neck neoplasms have a higher prevalence of methylation in comparison to a healthy control group (3,6,11,12). Sushma et al suggest a promoter hypermethylation panel for oral squamous cell carcinoma (OSCC) consisting of the following genes: PTEN and p16 (12), which can be detected by a tissue biopsy.…”
Section: Promoter Hypermethylationmentioning
confidence: 99%